Survival Following Tumor Recurrence in Children With Medulloblastoma. Issue 3 (April 2018) - Johnston, Donna L.; Keene, Daniel; Strother, Douglas; Taneva, Maria; Lafay-Cousin, Lucie; Fryer, Chris; Scheinemann, Katrin; Carret, Anne-Sophie; Fleming, Adam; Afzal, Samina; Wilson, Beverly; Bowes, Lynette; et al.
Abstract : Medulloblastoma is the most common malignant brain tumor in children. Published survival rates for this tumor are ∼70%; however, there is limited published information on outcome after disease recurrence. This was an observational study which included all persons under the age of 18 years diagnosed with medulloblastoma from 1990 to 2009 inclusive in Canada. Data collected included date of diagnosis, age at diagnosis, sex, stage, pathology, treatment, recurrence, and current status. Survival rates were determined. In total, 550 cases were ascertained meeting the study criteria. The overall survival rate at 1 year was 83.6%±1.7%, at 3 years 77.2%±1.9%, and at 5 years 72.5%±20%. The progression-free survival rates were 78%±1.9%, 70%±2.1%, and 69±2.1% at 1, 3, and 5 years from initial diagnosis. In total, 173 (31.2%) were reported to have had tumor recurrence and 23 (11.4%) of them were alive at the time of survey with an overall survival rate at 1 year of 38.3%±4%, at 2 years of 16.9%±3.3%, and at 5 years of 12.4%±2.8%. Our data confirm that children with recurrent medulloblastoma have a poor prognosis, supporting the need for novel treatment approaches for this group.